1995
DOI: 10.1302/0301-620x.77b5.7559710
|View full text |Cite
|
Sign up to set email alerts
|

Partial excision of the clavicle for nonunion in National Hunt Jockeys

Abstract: National Hunt jockeys suffer a disproportionate number of clavicular fractures and their return to riding may be considerably delayed by refracture and symptomatic nonunion, with obvious implications. We report six such cases in which excision of the clavicular fragment distal to the fracture was associated with an early return to work and no recurrent injury to the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Displaced clavicular midshaft fractures that predominated in the analyzed male samples are common in high‐velocity and contact sports (ibid.). A disproportionately high number of clavicular fractures have been recorded in jockeys that compete over steeplechase races (Balendra et al, 2007; Middleton et al, 1995). There have been striking differences in injury rates between amateur and professional jump racing jockeys.…”
Section: Discussionmentioning
confidence: 99%
“…Displaced clavicular midshaft fractures that predominated in the analyzed male samples are common in high‐velocity and contact sports (ibid.). A disproportionately high number of clavicular fractures have been recorded in jockeys that compete over steeplechase races (Balendra et al, 2007; Middleton et al, 1995). There have been striking differences in injury rates between amateur and professional jump racing jockeys.…”
Section: Discussionmentioning
confidence: 99%
“…Although few cases are documented and long-term follow-ups are lacking, most have yielded fair results. However, some patients continued to complain of pain and clicking at the resected end, while others have expressed dissatisfaction about the cosmetic appearance of a prominence in the anterior chest region 14. Through a literature search, Acus et al 11 were found to have published the largest series of proximal clavicle excisions up to date, although none of the 15 patients underwent the procedure because of symptomatic non-union of clavicular fracture.…”
Section: Discussionmentioning
confidence: 99%
“…7 Claviculectomy is a rare surgical procedure that has been performed for a variety of indications, such as tumors, infection, facilitation of surgical exposures, fracture nonunion, and severe pain. [11][12]14,[22][23] Lewis et al 12 concluded that patients who undergo radical en bloc resection of the clavicle can expect some weakness in shoulder abduction, flexion, and to a lesser extent, adduction. 12 These functional weaknesses may be clinically insignificant to the patient, depending on the activities of daily living.…”
Section: Discussionmentioning
confidence: 99%